Analysing The Factors Hampering Tanzanian Agricultural Export To The European Union - Sendalo, Francis Raphael; Bakhtiar, Ary; Mazwan, M. Zul (Universitas Muhammadiyah Jember, 2023)
The supply of Agricultural Products to the EU country has not been able to meet the consumers demand so that the fulfillment of demand, Agricultural production must be improved . This study aims to analyze the factors that influence Agricultural exports in Tanzania to the EU countries. The research method uses quantitative analysis techniques, namely Panel data regression. This research was conducted in Tanzania using secondary data from 2002-2020 obtained at the National Bureau of Statistics,World Bank and the Ministry of Agriculture and other literature related to research. Research variables include Value of Exports,exchange rates, GDP per capita, Proximity distance, and Ecolabling. The results showed that variables GDP per capita, milk exports, and milk production have a positive influence. Meanwhile, the exchange rate has negative influence for agricultural exports.